Pengaruh Ukuran Kantor Akuntan Publik, Audit Tenure dan Spesialisasi Kantor Akuntan Publik Terhadap Kualitas Audit - Rinjani Dewi Mayangsari; Aghan Yunardo Sazangka (Owner : Riset dan Jurnal Akuntansi, 2023)
This study aims to examine the effect of the size of the Public Accounting Firm, audit tenure, and Specialist Public Accounting Firm on audit quality. The sample used in this research is banking companies listed on the Indonesia Stock Exchange (IDX) for the period 2018 to 2020 which can be accessed via the Indonesian Stock Exchange website (www.idx.co.id). This research uses descriptive research with a quantitative approach. The sample selection method in this study used a purposive sampling technique, with a total sample of 119 data obtained from banking companies. This study uses the hypothesis of multiple regression analysis. The results of the study show that (1) KAP size has an effect on audit quality in banking companies listed on the IDX for the 2018-2020 period, whereas (2) Audit tenure has no effect on audit quality in banking companies listed on the IDX for the 2018-2020 period, and (3) KAP specialization affects audit quality in banking companies listed on the IDX for the 2018-2020 period.